Results of breeding work to create genotypes of winter peas with basic economically valuable traits in the conditions of Adygea - M. V. Kuzenko; K. K. Khatkov (Новые технологии)
The work shows the historical stages of breeding work to create adapted varieties of wintering peas to the soil and climatic conditions of the southern foothill zone of the North-Western Caucasus (Republic of Adygea). In the course of these studies, it was necessary to solve the problem of increasing the winter hardiness of the crop, grain resistance, resistance to viral and fungal diseases, and new varieties should show high yields of green mass and grain of good quality and be more early ripening. The first stages of research were aimed at collecting and studying the source material. In order to increase winter hardiness, winter-hardy pellets and white-flowered, weakly winter-hardy forms were used during hybridization. To increase seed resistance, multi-flowered samples and forms were used; increasing resistance to fungal and viral diseases was achieved by involving the most resistant samples in crosses. The use of highly productive samples in hybridization as the maternal form, and the earliest ripening ones as the paternal form, made it possible to solve the problem of creating varieties of wintering peas that combine early ripening with high yields of green mass and seeds. High-protein samples were involved in crossings to increase the protein content in green mass and grain. Mutant forms were obtained using chemical mutagens and pulsed concentrated solar and laser light. The volume of crosses carried out over the entire period amounted to 600 different combinations.As a result of breeding work on the creation and isolation of new genotypes of wintering peas, possessing a complex of positive economically valuable traits, a collection of 1950 samples was formed, including highly productive forms. A wintering pea variety ADS 85 adapted to local soil and climatic conditions has been created and released.